2020
DOI: 10.20473/jkl.v12i2.2020.87-96
|View full text |Cite
|
Sign up to set email alerts
|

Defecation Behavior in Elementary School Age Children Who Live Along the Kampar River Riau Province

Abstract: Introduction: Based on WHO reports, nine out of ten people who live in rural areas still defecate carelessly. The results of an initial survey conducted in November 2018 of 46 houses along the Kampar river in the village of Buluh China Riau Province, 42% of the community still open defecation, such as into the river. This study aims to get a picture of defecation behavior in elementary school age children who live along the river. Methods: This research was conducted in Buluh Cina Village, Siak Hulu District, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
3
0
3
Order By: Relevance
“…Sikap seseorang yang masih belum dianggap baik, maka rentan bagi orang tersebut untuk tetap berperilaku BABS (Zahtamal et al, 2020). Sikap seseorang dapat dipengaruhi beberapa faktor seperti adanya pengaruh dari tetangga untuk tidak melakukan BABS sehingga dapat menumbuhkan kebiasaan baru karena kesan yang ditinggalkan kuat.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Sikap seseorang yang masih belum dianggap baik, maka rentan bagi orang tersebut untuk tetap berperilaku BABS (Zahtamal et al, 2020). Sikap seseorang dapat dipengaruhi beberapa faktor seperti adanya pengaruh dari tetangga untuk tidak melakukan BABS sehingga dapat menumbuhkan kebiasaan baru karena kesan yang ditinggalkan kuat.…”
Section: Hasil Dan Pembahasanunclassified
“…Pengetahuan yang dimiliki individu apabila semakin tinggi atau banyak, maka seseorang tersebut akan semakin bagus dalam memanfaatkan jamban, begitu pula sebaliknya (Anggoro and Ningrum, 2015). Pengetahuan yang belum ideal atau belum berada pada kategori baik, dapat menyebabkan kerentanan masyarakat untuk tetap melakukan BABS (Zahtamal et al, 2020). Pengetahuan yang baik jika tidak didukung dengan faktor lain seperti adanya ketersediaan lahan, pendapatan yang cukup, air bersih, dan peran tenaga kesehatan maka masyarakat tidak akan membuat jamban sendiri di rumah mereka sehingga tidak bisa menimbulkan kebiasaan buang air besar yang baik (Arlin, Sudirman and Afni, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…This study aims to see students' perceptions of nonnatural disaster mitigation policies on vigilance of the spread of virtus Covid-19 in the Andalas University environment. This research is a descriptive survey (22). The study population was all students from the Department of Political Science, Faculty of Social and Political Sciences, Andalas University in Padang which is the best university outside Java for 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors contributed to such practice including lack of knowledge of its impact to health and limited financial capacity to build their own toilets (Gargita, Miswan, & Rosnawati, 2020;Junias, Mukono, & Purnomo, 2016;Putra & Selviana, 2017;Yulyani, Dina Dwi, & Kurnia, 2019). In addition, respondents found availability and proximity of river streams, bushes nearby their houses as 'enabling' factor for them to continue practicing OD behavior (O'Connell, 2014;Zahtamal, Chandra, Restila, & Restuastuti, 2020). Other study revealed traditional beliefs and norms such as sharing toilet with others may invite evil spirit, children's feces are not harmful, or accumulating feces into one spot create bad luck have significant and direct influence to school children defecating in the open (Adjibolosoo, Adongo, Tawiah-Yirenya, Ofori, & Afranie, 2017).…”
Section: Introductionmentioning
confidence: 99%